Depositional Environment Reconstruction and Diagenetic Evolution of Marly Carbonates in the Kepek Formation Based on Microfacies Analysis from the Rambutan River, Gunungkidul - Lathifah Kusuma Melati; Istiana; Mochammad Prahastomi (Jurnal Ilmiah Dinamika Rekayasa, 2026)
The Kepek Formation is a Neogene carbonate unit in the Southern Mountains of Java that records changes in depositional environments and diagenetic processes during the evolution of the carbonate basin. This study aims to reconstruct the depositional environment and diagenetic evolution of the Kepek Formation based on microfacies analysis of the Rambutan River outcrop, Gunungkidul Regency. The study involved measurement of a 14.6 m stratigraphic section, calcimetric analysis, thin-section petrography, microfacies analysis, planktonic foraminiferal biostratigraphy, and diagenetic analysis. The studied succession consists of clayey marl, limey marl, marl, marly limestone, and limestone with CaCO₃ contents ranging from 29.9% to 95.5%. Five microfacies were identified and correlated with the Ramp Microfacies Types (RMF), indicating that the Kepek Formation was deposited within a homoclinal carbonate ramp system comprising the open-marine inner ramp, mid-ramp, and outer ramp. The vertical alternation of microfacies records repeated migration of depositional belts in response to relative sea-level fluctuations during the Late Miocene–Early Pliocene. Diagenetic evolution progressed through the stages of eogenesis, mesogenesis, and telogenesis, which modified the original carbonate fabric and porosity after deposition. This study establishes a depositional and diagenetic evolutionary model for the Kepek Formation, demonstrating that the distribution of carbonate facies was controlled by repeated migration of depositional belts driven by relative sea-level fluctuations. These findings improve the current understanding of Neogene carbonate evolution in the Southern Mountains of Java by integrating microfacies, biostratigraphic, carbonate content, and diagenetic analyses.